The first principles calculations of Pt or Au doping on improving the detection of CO by ZnO using density functional theory / Micheal Mage Dorin Zalinda ... [et al.] - Dorin Zalinda, Micheal Mage (Penerbit UiTM (UiTM Press), 2024)
ZnO doped with Pt or Au (Pt/Au-ZnO) exhibits strong gas response at room temperature, making it a promising gas sensing material. Since carbon monoxide (CO) is one of the most hazardous gases in both daily work and life operations, it's critical to develop gas sensors with excellent stability, sensitivity, and selectivity for CO gas. The aim of this study is to investigate the structural and electronic properties of crystal ZnO using CASTEP calculation, and also to elucidate the effect of Pt/Au on ZnO as CO detection with validated functional exchange correlation GGA-PBE that implemented in CASTEP computer code. For each doped material, the composition was changed with 100% of Pt/Au and 0% of O, 80% of Pt/Au and 20% of O, 60% of Pt/Au and 40% of O, 40% of Pt/Au and 60% of O, and 20% of Pt/Au and 80% of O. The geometrical optimization and energy were calculated by GGA-PBE. It is believed that noble metal surface modification of metal oxide is the most practical and efficient way to enhance gas sensing. Because of their strong catalytic activity, noble metal nanoparticles have been demonstrated in multiple studies to enhance ZnO's sensing capabilities. Furthermore, by doping noble metals which are Pt and Au with ZnO, it provides the insight of developing gas sensors for CO detection by determining the formation energy and understanding the energy band structure and the density of states.